INFLUENCE OF COMMUNICATION AND COORDINATION IN PREVENTION OF FIRE MANAGEMENT TO THE PERFORMANCE OF EMPLOYEES OF THE FIRE MANAGEMENT AND RESCUE SERVICE SECTOR III TAMBORA - Zaini, Zaman; Sarbini, Achmad (International Peneliti Ekonomi, Sosial dan Teknologi, 2020)
The purpose of this sting is to know some of the influence of communication on the performance of firefighters condemned tambora, some of the influence of coordination on the performance of firefighters condemned Tambora, and some of the influence of communication and coordination. Together, the performance of firefighters was condemned by Tambora. The research method used in this research is a quantitative approach with statistical methods. The population of 70 officers, the sample number of 60 officers using the Slovin formula with a level of 5% blame. Data is obtained by the dissemination of questionnaires and documentation. Data analysis techniques use descriptive analysis, classical assumptions, multiple regression analysis and correlation analysis with the help of SPSS for Windows Release 23. The results of this study, on the t (partial) test of vaiabel communication obtained a significance value of 0.029, so that H1 was accepted. In variabel coordinated obtained significance value 0.000, and Test F (Simultaneous) shows that the significance value is 0.000, so H1 is accepted. Thus this research can be concluded that there is a communication influence on the performance of firefighters with a correlation of 51.1%, there is a coordination influence on the performance of firefighters and a correlation of 64.7% and the influence of communication and coordination together on the performance of fire employees. Fire in Tambora District. The percentage of communication and coordination variables can explain and improve the performance of firefighters in Tambora Subdistrict is 44.7% and the remaining 55.3% is influenced by other variables that are not included in the model.